Time to think: Subjective sleep quality, trait anxiety and university start time. (January 2019) - Norbury, Ray; Evans, Simon
Highlights: Poor quality sleep is related to mental health. A large proportion of students are chronically sleep deprived and this was more marked in first year students. Poor sleep is associated with increased anxiety. We recommend that a later start-time be adopted across the university sector. Better education on the importance of sleep quality is required. Examination time tables should avoid early morning test times. Abstract: Poor quality sleep is related to mental health and there is increasing interest in student wellbeing and mental health. The aim of the current study was to evaluate sleep quality, daytime dozing, anxiety proneness, chronotype and preferred start time in a sample of university students. A total of 546 university students (age range, 18–55) from two university located in South East England were included and completed an online survey. Participants' self-reported age, gender, year and field of study. Sleep quality, anxiety, daytime dozing, coffee/caffeine/tobacco use (coded as binary variables), preferred start time and chronotype were also recorded. Data were analysed using independent samples t -tests, chi-square, simple mediation-analyses and Analysis of Variance. Across the entire sample 46% percent of participants rated their sleep as fairly bad or very bad. Poor quality sleep was associated with significantly higher levels of anxiety which was not mediated by chronotype. Poor quality sleep is more prevalent in the first year of university and our sample endorsed a start time for university activities approximately 2 h later than currently timetabled. The current findings demonstrate that a large proportion of students are chronically sleep deprived, obtaining, on average, less than 7 h sleep per night on week days and this was more marked in first year students. In addition, we show that poor sleep is associated with increased anxiety. Based on the current evidence the authors suggest a review of current university timetabling and examination scheduling merits immediate consideration by policy makers and educators.